Relationship between cooling rate and microsegregation in bottom-chilled directionallysolidified ductile irons - Wen-Shiung, Chang; Chun-Ming, Lin (Journal of Mining and Metallurgy, Section B: Metallurgy, 2013)
This study explores the relationship between cooling rate and microsegregation of directionally solidified ductile iron. The unidirectional heat transfer system used in this research is made up of a copper mold kept chilled by circulating water and embedded in the bottom of Furan sand mold. Thermocouples are connected to the computer measuring system to record the cooling curves of the castings at a distance of 0, 30, 60 and 90 mm from the chilled copper mold surface. Alloys including Mn, Cr, Cu, Ni and Ti were added to the specimens. Electron microprobe analysis (EPMA) was employed to examine distribution of elements between the dendrite arms and nodular graphite. Results show that unidirectional heat transfer affects directly the solidification mode and microstructure of the casting. The cooling curves reveal that local solidification time increases with increasing distance from the chilled copper mold surface. Different solidification rates with corresponding microstructure and element segregation were observed in the same unidirectionally solidified casting. Local solidification time was closely related to element segregation. The effective segregation coefficient (Keff) calculated using the Scheil equation was found to vary stages of solidification and the actual segregation characteristics of complex alloys in general follow the Scheil equation.